Tantangan Sistemik Kompetensi Sdm Dan Implementasi Talent Management Terhadap Employee Engagement Di BPJS Ketenagakerjaan Mamuju, Sulawesi Barat - Mardilah Mahmud; Agus Halim (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze systemic challenges of human resource competencies and the implementation of talent management on employee engagement at BPJS Ketenagakerjaan Mamuju, West Sulawesi. The study adopts a qualitative descriptive approach based on literature review and secondary data without direct empirical investigation. Data were obtained from institutional reports, official publications, and relevant studies published within the last five years. The findings indicate that systemic competency challenges include mismatch between competencies and job demands, limited competency-based development systems, and adaptation to digital transformation. Suboptimal implementation of talent management affects employee engagement, particularly vigor, dedication, and absorption dimensions. This study concludes that strengthening HR competency systems and implementing structured, transparent, and sustainable talent management are essential to enhance employee engagement. The study provides theoretical and practical implications for HR management in public sector organizations.